78‐2: Improving The Flexibility of AMOLED Display through Modulating Thickness of Layer Stack Structure. Issue 1 (May 2016) - Niu, Yi-Fan; Liu, Sheng-Fa; Chiou, Ji-Yi; Huang, Ching-Yu; Chiu, Yi-Wen; Lai, Ming-Hsiang; Liu, Yen-Wei
Abstract : A robust methodology is established to predict the critical bending radius of a flexible AMOLED. According to the methodology, the critical bending radius of display manufactured by the same process could be reduced from 7 mm to 4mm by modulating the layer stack thickness.